2004
DOI: 10.1007/s00244-004-0073-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin and Respiratory Doses and Urinary Excretion of Alkylphosphates in Workers Exposed to Dimethoate During Treatment of Olive Trees

Abstract: This article describes a study of exposure to dimethoate during spraying of olive trees in Viterbo province in central Italy. Airborne concentrations of dimethoate were in the range 1.5 to 56.7 nmol/m(3). Total skin contamination was in the range 228.4 to 3200.7 nmol/d and averaged 96.0% +/- 3.6% of the total potential dose. Cotton garments afforded less skin protection than waterproof ones, which were in turn associated with higher skin contamination than disposable Tyvek overalls. Total potential doses and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Evaluation of skin exposure by means of filter paper pads and hand washing with 95% ethanol has likewise been reported in other studies [10][11][12][13][14][15][16]. The methods used to extract samples are fast and give good recovery of analyte and good precision within and between series.…”
Section: Discussionmentioning
confidence: 57%
“…Evaluation of skin exposure by means of filter paper pads and hand washing with 95% ethanol has likewise been reported in other studies [10][11][12][13][14][15][16]. The methods used to extract samples are fast and give good recovery of analyte and good precision within and between series.…”
Section: Discussionmentioning
confidence: 57%
“…However, compound-specific kinetics of inhaled pesticides was not characterized in our study. Second, our study assumed that the length of pesticide spraying time reflects the individual exposure levels, yet it lacked accurate dose evaluation, something which has been rarely investigated in occupational settings 15) . Factors such as application method, use of personal protective gear, or work practices related to hygiene influence exposure levels and appropriate exposure assessments are challenging given these complexities 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Some human volunteer studies revealed a correlation between external exposure to OP or pyrethroids and biological monitoring values [11][12][13] . However, only a few studies have estimated the individual exposure amount in occupational settings [14][15][16] , where factors influencing the exposure level usually vary; highly elaborate techniques were employed in these dose evaluation studies. Because only limited data are available in Japan on the relationship between the exposure to pesticide and its metabolite concentrations in urine among PCOs [17][18][19] , we conducted a preliminary field study to examine whether the levels of urinary metabolites reflect the length of pest control operations which we consider to be a crude substitute for pesticide exposure levels.…”
mentioning
confidence: 99%
“…But skin contamination may also occur due to a splash, spill or drift when handling an AP and contact with residue on application equipment, protective clothing or treated surfaces. When handling concentrated APs, hazard from skin absorption increases (Aprea et al, 2004;Lebailly et al, 2009;OECD, 2011;Fabian et al, 2012;MacFarlane et al, 2013;Fabian and Binder, 2015;Mieldazys et al, 2015).…”
Section: Routes Of Exposure To the Apsmentioning
confidence: 99%